Long-Term Follow-up of Functional and Radiographic Outcome After Revision Surgery for Fibula Malunion. Issue 1 (February 2022) - Birnie, Merel F. N.; Sanders, Fay R. K.; Halm, Jens A.; Schepers, Tim
Background. Ankle fractures are some of the most common injuries seen in the emergency department. Malunited ankle fractures are uncommon. Patients with malunion frequently present with multiple complaints. Radiographs often show abnormalities in anatomical alignment.Aim. To evaluate the anatomical alignment on radiographic imaging in patients with malunited ankle fractures. Secondary aims were to evaluate patient satisfaction after reconstruction and to investigate the relationships between radiological alignment and functional outcome.Methods. All consecutive patients (n = 25) treated for a fibula malunion between January 1, 2002, and September 1, 2017, were included. The primary outcome was anatomical alignment of the ankle mortise. The talocrural angle (TCA), talar tilt (TT), and medial clear space (MCS) were used to investigate to what extent revision surgery had improved alignment. The patient-related outcome measure consisted of the Olerud and Molander Ankle Score (OMAS). To assess quality of life (QoL) the EQ-5D-5L was used.Results. The median TCA was 78.4° before revision and 79.25° after revision; P = .297. The median TT was 2.95° before revision and 0.70° after; P < .001. The MCS before revision was 5.2 mm and 3.17 mm after; P < .000). The OMAS had a median of 67.5 points. Analysis of the QoL questionnaires yielded a score of 0.84 points.Conclusion. Anatomical alignment improves significantly after revision surgery of malunited ankles. Measurements of the TCA appeared less useful in determining the anatomical alignment. In our series, 60% of patients reported good to excellent results. The QoL scores of our patient were comparable to those in the healthy population in the Netherlands. Levels of Evidence: Level IV: Case series